The tick Ixodida: An unusual foreign body in the ear - Alazzawi, Sarmad; Omar, Rahmat; Raman, Rajagopalan (Royal Society of Medicine, 2016)
We report a patient with a hard tick in her left ear, adherent to the tympanic membrane.